The Influence of Corporate Social Responsibility, Reputation and Customer Satisfaction Toward Tourism Loyalty on Karanganyar Regency - I Gusti Putu Diva Awatara; Samsi Samsi; Anwar Hamdani; Linda Nur Susila (AIBPM Publisher, 2020)
This study aims to analyze the role of corporate social responsibility and support for tourist visitor loyalty which is mediated by visitor satisfaction in Karanganyar Regency. This research is a survey conducted in Karanganyar Regency. The sample used in this study was 100 respondents. The sampling method used was purposive random sampling. Data collection techniques used were questionnaire, observation and documentation. Data analysis techniques used research instrument tests that included validity and reliability tests; linearity test and path analysis test. The results of this study indicate that social responsibility and positive ownership of visitor satisfaction. Social responsibility, satisfaction and satisfaction of visitors to visitor loyalty. The influence of corporate social responsibility and commitment to visitor loyalty is mediated by visitor satisfaction.